Fabrication and characterisation of nanostructured zinc oxide thin films incorporated with nanorod arrays-based solar cells / Mohd Firdaus Malek - Malek, Mohd Firdaus (2017)
In this research, several types of solar cells have been successfully fabricated using zinc oxide-based nanoparticles (ZnO NPs) and ZnO-based nanorod arrays (ZnO NRAs). Both of ZnO NPs and ZnO NRAs were synthesised via novel dual sonication sol-gel immersion process. In this work, ZnO NRAs were grown on a seed layer by ultrasonic-assisted immersion technique while the seed layer, which consists of ZnO NPs were deposited by ultrasonic-assisted sol-gel dip-coating technique. The main points for this thesis are not only to successfully realise the controllable growth of ZnO NPs and ZnO NRAs but also investigate the structural, optical and electrical properties in detail by means of X-ray diffraction, field emission scanning electron microscopy, transmission electron microscope, energy dispersive X-ray spectroscopy, ultraviolet-visible-infrared spectrophotometry and two-probe current-voltage measurement system. There are several processing parameters such as dopant concentration, annealing temperature, growth time and various types of dopants which can be controlled were being optimised. The optimised growth parameters were applied to fabricate several solar cell devices which were dye sensitised solar cells (DSSCs), hybrid solar cells (HSCs), perovskite solar cells (PSCs) and inverted organic solar cells (IOSCs)…